Evolução da resistência à compressão de prismas de blocos de concreto: análise experimental e modelagem matemática - Oliveira, Afonso Henrique Lacerda Brito de (2016)
This paper presents an experimental study in order to assess the evolution of the compressive strength of masonry, throughout the ages, through the materials resistance study consisting of two structural concrete blocks and propose a mathematical model able to estimate compressive strength of the prisms at different ages. For this purpose, the compressive strength tests were performed and prisms modulus of elasticity without grout and with grout, in ages of 7, 14 and 28 days, using three different resistances blocks, two types of mortar of industrialized and two lines of grout , totaling 12 different types of prisms. Moreover, in these ages, mortar and grout was evaluated for compressive strength and modulus of elasticity. It also evaluated the evolution of the mortar resistance, depending on the molding method and form of the specimens. It adds that the prisms were evaluated regarding the interference of their nominal and effective dimensions in the result of the compressive strength test. From the analysis of the test results, there is no significant interference of the dimensions of the prisms on the results of the compressive strength test, and no significant differences in relation to the body-of-proof mortar format and the respective result of resistance compression. It was also observed that the compressive strength results after 14 days is very close to the value obtained after 28 days (greater than 80%). It was concluded that also influence of components in the final strength of the prisms can be analyzed at seven days, so that if, at 7 days, a resistance increased in block causes increase in resistance in the prism, this same effect is observed after 28 days; Likewise, if, at 7 days, a resistance increase in the grout causes a decrease in resistance in the prism, this same effect is observed after 28 days. Finally, this study was able to provide three expressions for estimating prisms Compressive strength at different ages (7, 14 and 28 days), with grout or not, from the compressive strength of the units.